2013
DOI: 10.1242/dev.082875
|View full text |Cite
|
Sign up to set email alerts
|

Functional dissection of the paired domain of Pax6 reveals molecular mechanisms of coordinating neurogenesis and proliferation

Abstract: To achieve adequate organ development and size, cell proliferation and differentiation have to be tightly regulated and coordinated. The transcription factor Pax6 regulates patterning, neurogenesis and proliferation in forebrain development. The molecular basis of this regulation is not well understood. As the bipartite DNA-binding paired domain of Pax6 regulates forebrain development, we examined mice with point mutations in its individual DNA-binding subdomains PAI (Pax6Leca4, N50K) and RED (Pax6Leca2, R128C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
76
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 93 publications
8
76
0
1
Order By: Relevance
“…This observation directly supports our model that Ey/Toy control growth of the eye-antennal disc and is consistent with studies in vertebrates that demonstrate roles for Pax6 in the proliferation of neural progenitors within the brain (53,(78)(79)(80). Earlier studies observed cells undergoing apoptosis in Pax6 singlemutant eye-antennal discs and showed that blocking cell death alone can partially rescue the head defects of the ey D and toy hdl mutants (46).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This observation directly supports our model that Ey/Toy control growth of the eye-antennal disc and is consistent with studies in vertebrates that demonstrate roles for Pax6 in the proliferation of neural progenitors within the brain (53,(78)(79)(80). Earlier studies observed cells undergoing apoptosis in Pax6 singlemutant eye-antennal discs and showed that blocking cell death alone can partially rescue the head defects of the ey D and toy hdl mutants (46).…”
Section: Discussionsupporting
confidence: 91%
“…Our results indicate that Ey and Toy promote proliferation of the eye-antennal disc and specification of the eye, while simultaneously repressing alternate nonocular fates. These results are consistent with a previous report showing that Pax6 is also required for the development of nonocular head structures in the flour beetle, Tribolium castaneum (51), and there is growing evidence in several systems that Pax6 promotes cell proliferation (52)(53)(54)(55). These observations suggest that the function of Pax6 has been conserved across 500 million years of animal development.…”
supporting
confidence: 93%
“…1) and chromatin immunoprecipitation experiments, it was demonstrated that distinct downstream target genes were preferentially bound by either subdomain in vivo and that the PAI subdomain has a role in decreasing cell mitoses while the RED domain has the opposite effect. It was concluded that the coactivation of both proliferative and anti-proliferative genes acts to fine-tune cell-cycle progression (Walcher et al, 2013). This supposition is supported by the finding that Pax6 directs cortical cell cycle progression in a regionally specific manner (Mi et al, 2013) and that it does so through simultaneous expression of downstream target gene sets through epigenetic regulation of chromatin condensation in interaction with dynamically competitive BAF subunits during the progression of neurogenesis (Tuoc et al, 2013).…”
Section: Pax6-mediated Control Of Neurogenic Proliferation and Differmentioning
confidence: 99%
“…Canonical Pax6[Pax6(−5a)] binds DNA primarily through the N-terminal portion of the paired domain (the PAI-domain), in Pax6(+5a) the DNA-binding potential of the C-terminal RED-domain predominates, whereas the 'paired-less' isoform utilizes the homeodomain for DNA binding (Epstein et al, 1994;Kleinjan et al, 2004;Kozmik et al, 1997;Mishra et al, 2002). All three isoforms recognize distinct DNA consensus sites and participate in the regulation of different developmental processes (Epstein et al, 1994;Haubst et al, 2004;Singh et al, 2002;Walcher et al, 2013). As we show here, all three isoforms can directly associate with Meis2.…”
Section: Multi-protein Network Involving Meis Family Members In the mentioning
confidence: 99%